Management optimizing the costs and duration time of the process in the production system - Krynke Marek (Production Engineering Archives, 2021)
This article proposes a method to support decision making from a cost management perspective in the initial stage of production planning. In a research analyzed the problem of selecting production resources for order realization. The research was based on computer simulation. The developed model focuses on the planning of the production process in the event that the products have not yet been produced and it is necessary to decide where to produce it (with what production resources) so that the total production costs are as low as possible. In this concept, the FlexSim simulation environment with a built-in optimization module was used to solve the problem. The basic steps of simulation model built were discussed, taking into account the necessary information and input data. The results show the impact of the application of selected simulation scenarios on the level of use of production resources, due to the minimization of the total production costs and the duration time of the production process.